2000
DOI: 10.1023/a:1005548619694
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Thirteen children (ages 5.6 to 11.2 years) with autism and symptoms of attention-deficit hyperactivity disorder (ADHD) participated in a double-blind, placebo-controlled crossover study of methylphenidate (0.3 and 0.6 mg/kg per dose). Eight subjects responded positively, based upon a minimum 50% decrease on the Conners Hyperactivity Index. Ratings of stereotypy and inappropriate speech, which are often associated with autistic core features, also decreased. However, no changes were found on the Child Autism Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(49 citation statements)
references
References 21 publications
1
46
0
1
Order By: Relevance
“…Other commonly used treatments for ASD include other antipsychotic agents [606-608], psychostimulants (for example, methylphenidate), which generally upregulate norepinephrine and/or DA function and reduce hyperactivity but have a relatively poor side-effect profile [609,610], and naltrexone, a DA modulator [607,611]. …”
Section: Reviewmentioning
confidence: 99%
“…Other commonly used treatments for ASD include other antipsychotic agents [606-608], psychostimulants (for example, methylphenidate), which generally upregulate norepinephrine and/or DA function and reduce hyperactivity but have a relatively poor side-effect profile [609,610], and naltrexone, a DA modulator [607,611]. …”
Section: Reviewmentioning
confidence: 99%
“…A statistically significant moderate reduction in hyperactivity symptoms was also observed 69. Handen et al70 conducted the second RCT of methylphenidate in 13 children diagnosed with autism or PDD not otherwise specified with symptoms of attention-deficit hyperactivity disorder over 7 days using a double-blind, placebo-controlled, cross-over design. Subjects ranged in age from 5.6–11.2 years (mean = 7.4 years).…”
Section: Resultsmentioning
confidence: 92%
“…The two RCTs69,70 produced significant results, but their sample sizes were small and the study duration was relatively short 11…”
Section: Resultsmentioning
confidence: 99%
“…Relative to the only other small ( n ⩽13), controlled studies of stimulants in ASD, our sample is more homogenous with respect to sex, ethnicity, treatment history and diagnosis. 11, 12 Capitalizing on the strengths of our design, we were able to examine genetic effects observed under optimal treatment conditions, as determined by blinded assessments and multiple raters.…”
Section: Discussionmentioning
confidence: 99%
“…Despite common use of stimulants for ASD, 7, 8 variable effects and reduced tolerability was suggested from small early studies, 9, 10, 11, 12 but no moderators of response have been reported. In the largest stimulant trial in ASD, the Research Units on Pediatric Psychopharmacology (RUPP) Autism Network (2005) found methylphenidate (MPH) was superior to placebo in reducing ratings of hyperactivity, 13, 14 but only half (35/72; 49%) were considered clinical responders.…”
Section: Introductionmentioning
confidence: 98%